Simultaneous Imaging of Dopants and Free Charge Carriers by Monochromated EELS - Yang, Hongbin; Konečná, Andrea; Xu, Xianghan; Cheong, Sang-Wook; Batson, Philip E; García de Abajo, F Javier; Garfunkel, Eric (ACS nano, 2022)
Doping inhomogeneities in solids are not uncommon, but their microscopic observation and understanding are limited due to the lack of bulk-sensitive experimental techniques with high enough spatial and spectral resolution. Here, we demonstrate nanoscale imaging of both dopants and free charge carriers in La-doped BaSnO3 (BLSO) using high-resolution electron energy-loss spectroscopy (EELS). By analyzing high- and low-energy excitations in EELS, we reveal chemical and electronic inhomogeneities within a single BLSO nanocrystal. The inhomogeneous doping leads to distinctive localized infrared surface plasmons, including a previously unobserved plasmon mode that is highly confined between high- and low-doping regions. We further quantify the carrier density, effective mass, and dopant activation percentage by EELS and transport measurements on the bulk single crystals of BLSO. These results not only represent a practical approach for studying heterogeneities in solids and understanding structure-property relationships at the nanoscale, but also demonstrate the possibility of infrared plasmon tuning by leveraging nanoscale doping texture.
Keywords: inhomogeneity; carrier effective mass; high-mobility oxide; band gap; infrared plasmonics; doped semiconductor; monochromated electron energy-loss spectroscopy